The whole treatment process and thinking of a patient with NUT carcinoma of the parotid gland: a case report - Fu, Shujuan; Wang, Zhiying; Li, Cunya; Li, Yun; Zhang, Ke; Zhong, Zhixian; Zhong, Yi (Frontiers in Oncology, 2023)
Background: Primary nuclear protein in testis (NUT) carcinoma is a rare malignant tumor originating from the salivary glands that usually occurs in midline structures, such as the head and neck, and has been identified in young patients. Progression of NUT carcinoma is rapid, and there is a high degree of malignant invasion. The median survival time of NUT carcinoma patients is 6 to 9 months, and 80% of the patients die within 1 year after diagnosis. Case description: This case report summarizes the treatment of a 36-year-old male patient with NUT carcinoma of the right parotid gland. The overall survival of the patient was 2 years. We also discuss the applications and outcomes of immune checkpoint inhibitor and targeted therapy combination regimens in the treatment of NUT carcinoma. Conclusion: We suggest that targeted therapy combined with immunotherapy which has long-term clinical benefits and targeted therapy which has high clinical response rate(immunotherapy + dual-targeting three-drug regimens) is an ideal choice for the treatment of patients with rare and/or refractory tumors and will not compromise patient safety.